Association of oral health awareness and practice of proper oral hygiene measures among Saudi population: a systematic review - Reham AlJasser; Aljoharah Alsinaidi; Noor Bawazir; Lama AlSaleh; Aseel AlOmair; Haifa AlMthen (BMC, 2023)
Abstract Background Several studies have proven that increasing oral hygiene knowledge correlates with good oral health status compared to those who lack this knowledge. Therefore, the aims of the study to evaluate the overall oral health awareness among the Saudi population based on knowledge and practice of proper oral hygiene measures. Methods A systematic review was performed according to the Preferred Reporting Items for Systematic Reviews guidelines. Cross-sectional, cohort, and case-control studies were included in the study and framed into a PICO question. Initially, a search was conducted on PubMed/Medline, Google Scholar, and Cochrane databases. Four independent reviewers screened the identified titles, abstracts, and full texts. Cohen's Kappa score was used to evaluate the level of agreement between the reviewers. Results Forty cross-sectional studies and one prospective cohort study were included. Several studies showed that most students across all departments of universities knew the protective effects of fluoride on teeth. Two studies assessing the attitude and practice of oral hygiene found that most students knew that poor oral health leads to gum disease, and 59.1% were aware of maintaining oral hygiene using a toothbrush and paste. Most participants knew the importance of oral and dental care before pregnancy and how to reduce dental problems during pregnancy. Pregnant women clean their teeth daily and consider brushing and using toothpaste essential for pregnant women. Studies on oral hygiene practices of patients with diabetes reported that flossing habits were rated less important and most of their respondents never flossed their teeth. Conclusion Strong correlation between oral health knowledge and practices was observed, with the higher the knowledge level, the better the practice. Therefore, new technologies and strategies must be tested for an effective oral health system. Trial Registration A protocol was specified and registered with the International Prospective Register of Systematic Reviews (PROSPERO) on August 2020 (registration number CRD 42,020,200,373).